Energy cost and parmesan cheese. An overview in the different energy fluxes needed to produce a parmesan wheel. Issue 1 (1st November 2022) - Puglia, Marco; Allesina, Giulio; Pedrazzi, Simone; Raguzzoni, Filippo
Abstract: Agriculture is responsible for up to 30% of the greenhouse gases emission, and cattle breeding is the main contributor making up almost 10% of the total. For this reason, this sector is a key player toward a complete decarbonization. To take the proper action to reduce climate impact of cattle breeding, it is necessary to know the energy requirements of the industry. This work focuses on the energy mapping of a parmesan cheese production, with reference to an agricultural company situated in Modena province with about six hundred animals. Knowing the electrical and thermal energy requirements to produce a wheel of cheese gives the possibility to the farmers to identify and reduce the energy wastage as well as starting the implementation of a strategy for fossil fuel substitution. In this study, a comprehensive monitoring campaign is presented together with the proposal of some possible improvements. The analysis showed that, considering the actual situation, about 64 kWh of electrical energy and 94 kWh of thermal energy are needed to produce a parmesan cheese wheel, while the fuel used to feed the agricultural machinery (e.g., tractors) accounts for around 174 kWh. In this context, the implementation of biogas and solar photovoltaic can greatly contribute to reduce the dependence on fossil fuels.